Utilization of Big Data in Increasing the Competitiveness of MSMEs - Qibtiyana, Mariyatul; Ali, Hapzi (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
MSMEs play a vital role in the Indonesian economy with a contribution of 61.07% to GDP and absorbing 97.2% of the workforce. In the digital era, MSMEs face intense global competition. To remain competitive, they need to carry out digital innovation to increase efficiency and competitiveness. HR and capital competency are also crucial in determining the quality and competitiveness of MSMEs. Big Data is important in managing large and complex information, helping MSMEs increase global competitiveness. This research highlights the role of Big Data, digital innovation, quality of human resources and capital in increasing the competitiveness of MSMEs. The methods used include literature study and observation. The research results show that Big Data and digital innovation can increase the competitiveness of MSMEs by optimizing cost and differentiation strategies. Good quality human resources improve business capabilities. Adequate capital is significant in the development of MSMEs. This research emphasizes the importance of information technology, Big Data, digital innovation, quality of human resources and capital in increasing the competitiveness of MSMEs in the digital era.